(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This scientific article examines the pedagogical and methodological aspects of using interactive games in teaching English in primary classes. Special attention is paid to the role of game-based technologies in increasing learners’ motivation, developing communicative skills, enriching vocabulary, and improving speaking abilities. The article analyzes the psychological characteristics of primary school pupils and justifies the effectiveness of interactive teaching methods. In addition, practical examples of interactive games used in English lessons are presented. The results of the study indicate that the systematic use of interactive games significantly improves the quality of English language learning and fosters a stable interest in foreign language acquisition.